Control ciudadano a la prestación del servicio de urgencias en la IPS Centro Policlínico S. A. Medellín (2010)
ABSTRACT: This article presents the findings and analysis of the main qualitative and quantitative research performed on the IPS Policlinic Center in the city of Medellin named “Citizen control on the emergency services provided by the IPS Policlinic Center S.A., Medellín”. IT also present reflections on key issues based on fundamental aspects for the execution of current regulations of services provided during emergencies, improving the quality of life of the users of this IPS. The state of the art on designing and making the strategic planning for the emergency health services portfolio was presented. The methodological tools for collecting information were centered on inspection processes of the facilities, surveys, interviews with users and employees, and the non-participant observation of students in research training. The results obtained indicate aspects to be improved such as factors of quality, aspects related to human fundamental rights to life and health consistent with the needs and conditions of users and in accordance with the standards set in this context with the need to train students on a participative culture education, beginning with the undergraduate and the citizens in general.